Historical Trends and Regional Differences in All-Cause and Amenable Mortality Among American Indians and Alaska Natives Since 1950 - Kunitz, Stephen J. (American Public Health Association, 2014)
American Indian and Alaska Native (AI/AN) death rates declined over most of the 20th century, even before the Public Health Service became responsible for health care in 1956. Since then, rates have declined further, although they have stagnated since the 1980s. These overall patterns obscure substantial regional differences. Most significant, rates in the Northern and Southern Plains have declined far less since 1949 to 1953 than those in the East, Southwest, or Pacific Coast. Data for Alaska are not available for the earlier period, so its trajectory of mortality cannot be ascertained. Socioeconomic measures do not adequately explain the differences and rates of change, but migration, changes in self-identification as an AI/AN person, interracial marriage, and variations in health care effectiveness all appear to be implicated.